Friendship Network in the Classroom: Parents Bias and Peer Effects - Fabio Landini; Natalia Montinari; Paolo Pin; Marco Piovesan (Lund University, School of Economics and Management, Department of Economics, 2014)
We interview both parents and their children enrolled in six primary schools in the district of Treviso (Italy). We study the structural differences between the children network of friends reported by children and the one elicited asking their parents. We find that the parents' network has a bias: parents expect peer effects on school achievement to be stronger than what they really are. Thus, parents of low-performing students report their children to be friends of high-performing students. Our numerical simulations indicate that when this bias is combined with a bias on how some children target friends, then there is a multiplier effect on the expected school achievement.
Keywords: D85; I21; Z13; 330; social networks; primary school; friendships; parents' bias; homophily; peer effects; Bonacich centrality